Efek Multiplier Dana Desa di Masyarakat Tani Desa Perbatasan NKRI-RDTL Kabupaten Timor Tengah Utara - Boanerges Putra Sipayung; Umbu Joka (Fakultas Pertanian, Universitas Timor, 2021)
Village funds provided by the Central Government to Village Governments are aimed at equitable distribution of the Indonesian economy. The Village Government is expected to be able to manage village funds to accelerate Indonesia's development, especially in disadvantaged areas. This study aims to analyze the multiplier effect of village funds in the border villages of the Republic of Indonesia- Democratic Republic of Timor Leste, North Central Timor Regency. The research was conducted in the border village of the Republic of Indonesia-Democratic Republic of Timor Leste in June-August 2020. The method used in this research is quantitative descriptive. The results of this study indicate that the multiplier effect rate in the research village is below 1.5. This shows that the use of village funds until 2020 has not been optimal because the economic activities carried out in border communities in North Central Timor Regency are still relatively low.